Local housing market and transportation improvements: The case of cul de sac and extremely remote localities - Vifill Karlsson (European Regional Science Association (ERSA), 2010)
In this paper, I examine the relationship between housing prices and transport improvements in case of tunnel in a locality in an extremely remote area of Iceland - a village far north called Siglufjörður. It have been documented that transportation improvements tend to influence housing prices, due to the general consumer preference for access over amenity value. I will examine whether this relationship holds in case of cul de sac in an extremely remote community in Iceland. A macro panel data set from Iceland will be used. It provides several essential variables for 79 municipalities in Iceland from 1981 through 2006. The results suggest that the impact is negligible against housing prices in this case. Further inspection shows that the price is sticky in the most relevant region, but the quantity is flexible. Thus, the estimation of the model will be repeated as an inverse demand function, where the housing price as exogene variable is replaced by sales quantity.
Keywords: R40; R21; R41; C23; 330; Housing prices; Transportation improvements; Distance gradient; Local